Innovation in Public Organizations: Do Public Service Motivation and Organizational Climate Play a Role? - Sahadewi, Nella Prapita; Pusparini, Elok Savitri (Jurnal Maksipreneur, 2025)
COVID-19 and digitalization brought new challenges for organizations. Organizations needed to be agile to face these challenges. Innovation was the key for organizations to sustain their presence in the business world. This study examined the impact of public service motivation (PSM), organizational climate (OC), and psychological empowerment (PE) on innovative work behavior (IWB) in a public organization. Using a quantitative approach with Structural Equation Modeling (SEM) in LISREL 8.8, the results indicated that PSM and OC have a positive effect on PE. PE, in turn, enhanced IWB. Mediation analysis showed that PE partially mediated the relationship between the independent variables and IWB. The findings suggested that fostering creativity, autonomy, and recognition within the organization is key to enhancing innovation.